L’Anatman nell’insegnamento del Buddha: orizzonte nihilista o linea di dialogo interreligioso? - Giuliano, Salvatore (Alpha Omega, 2013)
The spiritual path that led the young Siddhartha to become the Buddha (the Enlightened One), begins from the experience of pain present in human life. From here begins for him a journey of discovery that will lead to the denial of the Atman, the central concept of Hindu spirituality, by means of which it sketches out the individual spiritual principle, very similar to what Aristotelian-Thomistic metaphysics called “soul”. This denial has led many to consider Buddhism as a predominantly atheistic system whose horizon is lost in the ocean of nothingness. The Buddhist position, however, should be reconsidered in the cultural and social context of nascent Buddhism and that of what it later became. Such an understanding will lead the A. in the present contribution to reconsider the denial of the Atman itself not as a preliminary to the denial of God, but as an introduction to an approach to transcendence different from that present in the great monotheistic religions . Such an approach can become for all seekers of the Eternal a bridge for dialogue and a place of meeting between them.